FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN (Students' Journal of Accounting and Banking, 2014)
This study analyzes the factors that affect profitability in the banking company are listed in Indonesia Stock Exchange in 2010 to 2012. Variables used in this study are third party funds (DPK), Capital Adequacy measured by Capital Adequacy Ratio (CAR), Credit Risk measured by Non Performing Loan (NPL) and Liquidity measured by Loan to Deposit Ratio (LDR). These samples were selected using a method purposing sampling with a sample size of data 78. Types of data used are secondary data from annual report obtain from www.idx.co.id. The method of analyis used is multiple regression analysis. This study results that DPK have a positive and significant effect on ROA, CAR positif and no significant effect on ROA, NPL positive and no significant effect on ROA then LDR positive and no significant effect on ROA.Keywords: DPK, CAR, NPL, LDR, ROA